The style of Adam, first artist and first masterwork. Metaphysics and aesthetics in the birth of Ortega’s vital reason - Nigris, Francesco de (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
The main orteguian’s idea that «my life» is «reason», radically different from the phenomenological conception of reason that establishes Husserl in Ideen, mainly founded in being. Vital reason is theory of man as its circumstantial project; its unifying thread comes from an aesthetic reflection especially aimed at understanding realisms and idealisms, and whose philosophical consequences will be crucial.
Keywords: Ortega; life; vital reason; art; aesthetics